Safety and Efficacy of Roxadustat for Anemia in Patients With Chronic Kidney Disease: A Meta-Analysis and Trial Sequential Analysis - Liu, Chao; Fu, Zhangning; Jiang, Jiawei; Chi, Kun; Geng, Xiaodong; Mao, Zhi; Song, Chengcheng; Sun, Guannan; Hong, Quan; Cai, Guangyan; Chen, Xiangmei; Sun, Xuefeng (Frontiers in Medicine, 2021)
Background: Roxadustat, a hypoxia-inducible factor prolyl-hydroxylase inhibitor (HIF-PHI), has been used to treat anemia in patients with chronic kidney disease (CKD). However, its safety and efficacy remain controversial. Methods: PubMed, EMBASE, Science Citation Index, Cochrane Central Register of Controlled Trials, and Clinical Trial Registries databases were searched for relevant studies published up to April 2021. We identified randomized controlled trials (RCTs) comparing roxadustat with placebo or erythropoiesis-stimulating agents (ESA) in anemia patients with CKD with or without dialysis. Results: Eleven studies (containing 12 clinical trials) including 6631 patients met the inclusion criteria. In nondialysis-dependent (NDD-) CKD and dialysis-dependent (DD-) CKD patients, the total adverse events were not significantly different between the roxadustat and control (placebo or ESA) groups (relative risk (RR) = 1.02, 95% confidence interval (CI) = 1.00, 1.04, P = 0.08, and RR = 1.22, 95% CI = 0.91, 1.64, P = 0.18, respectively), and the TSA confirmed the result in NDD-CKD groups. No significant differences in hyperkalemia and infection incidences were found between roxadustat and placebo in DD-CKD groups. The pooled results showed that roxadustat significantly increased the hemoglobin response rate compared with placebo in NDD-CKD group and had an effect similar to that of ESA in DD-CKD group. However, iron metabolism parameters seemed not to be obviously optimized by roxadustat. Conclusion: Roxadustat can be safely used in CKD patients. Oral roxadustat was more effective than placebo as a therapy for anemia in NDD-CKD patients and noninferior to ESA on correcting anemia in DD-CKD patients. However, additional clinical trials are still needed to further prove whether roxadustat can optimize iron metabolism.